International Equity Flows and Speculative Bubbles: Some Empirical Evidence for South-East Asia - Christian Pierdzioch; Renatas Kizys (Verein für Socialpolitik, 2010)
We analyzed the links between international equity flows and speculative bubbles in the equity markets of six South-East Asian countries over the period 19912006. Based on a cointegration analysis, we found signi?cant equilibrium cointegration links between international equity flows and speculative bubbles. Before the Asian economic and financial crisis, an increase in speculative bubbles was accompanied by a decrease in net capital outflows. Our results are consistent with theories that predict that speculative bubbles absorb domestic savings in financially underdeveloped countries.
Keywords: G15; F37; 330; Speculative bubbles; International equity flows; South-East Asia; Cointegration analysis